Doing Business in Colombia 2010 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in Colombia 2010 is the second subnational report of the Doing Business series in Colombia. In 2007, quantitative indicators on business regulations were created for 13 cities and departments. This year, Doing Business in Colombia 2010 expands the analysis to a total of 21 cities and documents progress in the 13 cities previously measured. The data for Bogotá and the rest of the world are based on the indicators in Doing Business 2010: Reforming through Difficult Times, the seventh in a series of annual reports published by the World Bank and the International Finance Corporation. Doing Business investigates the regulations that enhance business activity and those that constrain it. The cities and departments covered in Doing Business in Colombia 2010 were selected together with the National Department of Planning and the Ministry of Trade, Industry and Tourism and are the following: Armenia (Quindío), Barranquilla (Atlantico), Bogota (Distrito Capital), Bucaramanga (Santander), Cali (Valle Del Cauca), Cartagena (Bolívar), Cucuta (Norte de Santander), Ibague (Tolima), Manizales (Caldas), Medellin (Antioquia), Monteria (Cordoba), Neiva (Huila), Pasto (Narino), Pereira (Risaralda), Popayan (Cauca), Riohacha (La Guajira), Santa Marta (Madgalena), Sincelejo (Sucre), Tunja (Boyaca), Valledupar (Cesar), Villavicencio (Meta). Regulations affecting six stages of the life of a business are measured at the subnational level in Colombia: starting a business, dealing with construction permits, registering property, paying taxes, trading across borders and enforcing contracts. These indicators have been selected because they cover areas of local jurisdiction or practice. The data in Doing Business in Colombia 2010 are current as of July 2009.